Pola Pengobatan Dan Analisis Potensi Interaksi Obat Pada Pasien Anak Demam Berdarah Dengue (Dbd) Di Rumah Sakit Kalimantan Timur - Helda Rahma; Muthia Dewi Marthilia Alim (Bali Health Published Journal, 2023)
Background: Dengue hemorrhagic fever is caused by transmission of the dengue virus by the Aedes aegypti mosquito. Dengue hemorrhagic fever is common in tropical countries such as Indonesia, where new cases are found every year. According to WHO that dengue fever is the leading cause of hospitalization for children. Dengue hemorrhagic disease is more susceptible to infection in children because the child's immune system is still very weak, so the virus is easy to multiply quickly in the body. Knowing the pattern of treatment and analysis of potential drug interactions in pediatric patients with dengue hemorrhagic fever at the East Kalimantan Hospital. Methods: The research is non-experimental observational with a descriptive research design. The approach method used is the cross sectional method. Identification of data collection is carried out retrospectively, by taking sources from medical records for the years 2020-2021. Results: Of  the 47 patient samples, the most cases were male patients as many as 27 patients (57%) with the age of 11 years as many as 11 patients (23%) with a length of stay of less than 7 days as many as 45 patients (96%). Based on the pattern of treatment, the most widely used therapy was the rehydration group (RL) 28 patients (60%). In the case of drug interactions occurred as many as 2 cases (3%). Conclusion: In this study show that there are cases of drug interactions.